2011
DOI: 10.1016/j.gene.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of the Ixodes scapularis degradome

Abstract: Parasitic encoded proteases are essential to regulating interactions between parasites and their hosts and thus they represent attractive anti-parasitic druggable and/or vaccine target. We have utilized annotations of Ixodes scapularis proteases in gene bank and version 9.3 MEROPS database to compile an index of at least 233 putatively active and 150 putatively inactive protease enzymes that are encoded by the Ixodes scapularis genome. The 233 putatively active protease homologs hereafter referred to as the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 128 publications
1
38
0
Order By: Relevance
“…At the time of this study, protease families that were encoded by A. americanum were not enumerated, presumably because its genome had not been sequenced. However, analysis of annotated sequences from I. scapularis showed that the tick might encode for all protease categories: aspartic, cysteine, serine, metallo-, and threonine proteases (79). Here, we found that A. americanum secretes at least 94 proteases in saliva during feeding.…”
Section: Resultsmentioning
confidence: 99%
“…At the time of this study, protease families that were encoded by A. americanum were not enumerated, presumably because its genome had not been sequenced. However, analysis of annotated sequences from I. scapularis showed that the tick might encode for all protease categories: aspartic, cysteine, serine, metallo-, and threonine proteases (79). Here, we found that A. americanum secretes at least 94 proteases in saliva during feeding.…”
Section: Resultsmentioning
confidence: 99%
“…Ticks used in validation of RNAi silencing were sampled at 48 h to ensure that the ticks were alive and could attempt to feed. Tick actin PCR primers (Mulenga et al, 2009) were used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the proteases here are likely associated with tick feeding regulation in that 75% (25/33) were detected between 24-120 h during tick feeding except for seven that were identified only in SD (S2 Table). Nearly 40% of proteases in the I. scapularis genome are metalloproteases [68]. Whether or not the observation in this study that majority of proteases in I. scapularis tick saliva are metalloproteases reflects the protease composition in I. scapularis genome or it is a physiological event, is unknown at this point.…”
Section: Majority Of Proteases In I Scapularis Saliva Are Metallopromentioning
confidence: 74%